CHINA’S RESPONSE TO U.S. ARMS SALES TO TAIWAN FROM 2021 TO 2025 - Frenki Setiawan; Indrawati (SOSIOEDUKASI, 2026)
This study examines China’s response to U.S. arms sales to Taiwan during the 2021–2025 period. China views these arms sales as a threat to the One-China principle, its sovereignty, territorial integrity, the stability of the Taiwan Strait, and its national strategic interests. This study aims to analyze the forms of China’s responses, explain its shift from diplomatic measures to legal and economic instruments, and interpret this pattern through the Balance of Threats framework. Using a descriptive qualitative approach and a literature review method, this study examines official documents, arms sale notifications, Chinese regulations, government statements, and relevant academic literature. The findings indicate that China’s responses have intensified in form, intensity, and institutional scope, ranging from diplomatic protests to the enforcement of the Anti-Foreign Sanctions Law, the use of the Unreliable Entities List, and sanctions against U.S. defense companies and their senior executives. These responses reflect China’s perception of threat, which is based on U.S. aggregate power, Taiwan’s geographical proximity, Taiwan’s evolving military capabilities, and U.S. strategic intentions in the Indo-Pacific region. This study contributes to the understanding of China’s balancing behavior by demonstrating that its responses are not only diplomatic in nature but are also increasingly legal and economic in nature.